Satisfaction of Aged Users with Mobility Assistive Devices: A Preliminary Study of Conventional Walkers - Boiani, Josieli Aparecida Marques [UNESP]; Sandnes, Frode Eika; Paschoarelli, Luis Carlos [UNESP]; Medola, Fausto Orsi [UNESP] (Springer Nature, 2020)
Elderly users’ satisfaction with their walkers was evaluated. A sample of 13 institutionalized aged participants were interviewed and responded to the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST 2.0) questionnaire, with eight questions that address their level of satisfaction with different aspects of the device. In general, the users reported to be satisfied with their device, with the highest levels of satisfaction with durability and easiness of use. The lowest scores were associated with device weight, ease of adjusting and device stability and safety. The users’ indicated the device safety, easiness of use and comfort as the most relevant aspects of the device. Elderly users’ satisfaction with their mobility devices is likely to correlate with users’ device needs and expectations.
Keywords: Assistive Technology; Elderly; Mobility; Satisfaction; Walkers